2010
DOI: 10.1016/j.yjmcc.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate attenuates myocardial contractility through augmentation of repolarizing Kv currents

Abstract: There is considerable evidence to support a role for lipotoxicity in the development of diabetic cardiomyopathy, although the molecular links between enhanced saturated fatty acid uptake/ metabolism and impaired cardiac function are poorly understood. In the present study, the effects of acute exposure to the saturated fatty acid, palmitate, on myocardial contractility and excitability were examined directly. Exposure of isolated (adult mouse) ventricular myocytes to palmitate, complexed to bovine serum albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 58 publications
(80 reference statements)
2
40
1
Order By: Relevance
“…Several studies have suggested that FAs or FA-mediated changes may influence myocardial calcium handling (17,47,24). The present study supports this view by showing that elevated FAs increase the oxygen cost for EC coupling.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Several studies have suggested that FAs or FA-mediated changes may influence myocardial calcium handling (17,47,24). The present study supports this view by showing that elevated FAs increase the oxygen cost for EC coupling.…”
Section: Discussionsupporting
confidence: 89%
“…The present study supports this view by showing that elevated FAs increase the oxygen cost for EC coupling. In cardiomyocytes, elevated palmitate has been reported to decrease Ca 2ϩ transients and fractional shortening (16,24). Whereas Fauconnier et al (16) reported that FA reduced SR Ca 2ϩ content and linked the changes in Ca 2ϩ handling and cell shortening, Haim et al (24) reported that these changes were not associated with altered SR Ca 2ϩ content but to increased peak outward voltage-gated K ϩ current amplitudes, leading to shortening of the action potential duration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 The three main metabolic substrates of the heart are carbohydrates, fatty acids, and ketone bodies with exogenous fatty acids accounting for 60%-70% of the energy production in the normal heart. 35 In health, the myocardium increases fatty acid metabolism with an acute reduction in mechanical function, 36 but conversely acute reduction in myocardial fatty acid metabolism in cardiomyopathy is also associated with impaired function. 37 In the case of pressure overload, we found in studies using the SHR an increased reliance on carbohydrate oxidation in an attempt to maintain contractile function with a decline in fatty acid and oxygen utilization.…”
mentioning
confidence: 99%